Intermodal interference in optical fibres - Ivan Martincek; Ivan Turek; Milan Dado; Karol Grondzak; Slavomir Cernicky (Communications - Scientific letters of the University of Zilina, 2000)
In this paper the results of a theoretical analysis and practical investigation of mode interference in single mode optical fibres are described. It is shown that inter-modal interference is a sensitive parameter depending on the quality of an index profile or geometrical parameters of optical fibre. The comparison of experimental and theoretical values of mode interference indicates that the measurement of interference could be used for testing how the real refractive index profile of investigated fibre corresponds with the refractive index profile assumed at the calculation (step-index profile).